1981
DOI: 10.3758/bf03207375
|View full text |Cite
|
Sign up to set email alerts
|

Apparent contrast of suprathreshold gratings varies with stimulus orientation

Abstract: Human contrast sensitivity is known to vary with both stimulus spatial frequency and orientation. Previous research has indicated, however, that the apparent contrast of a sinusoidal grating is independent of spatial frequency at suprathreshold levels. We have found that the apparent contrast of suprathreshold gratings is not independent of its orientation. Observers adjusted the apparent contrasts of vertical and oblique gratings to match a 40% standard. Contrast match deviations were found at a number of spa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
4
0

Year Published

1981
1981
2002
2002

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Perceptual research in a variety of settings has shown decrements in performance when stimuli are oriented at oblique angles (for review, see Appelle, 1972). For example, both resolution (Berkley, Kitterle, & Watkins, 1975;Bowker & Mandler, 1981) and vernier (Corwin, Moskowitz-Cook, & Green, 1977) acuity are impaired when the stimuli are oriented at angles intermediate to the horizontal and vertical axes. (3) Displacements in oblique directions might be smaller in magnitude than displacements in horizontal and vertical directions.…”
mentioning
confidence: 99%
“…Perceptual research in a variety of settings has shown decrements in performance when stimuli are oriented at oblique angles (for review, see Appelle, 1972). For example, both resolution (Berkley, Kitterle, & Watkins, 1975;Bowker & Mandler, 1981) and vernier (Corwin, Moskowitz-Cook, & Green, 1977) acuity are impaired when the stimuli are oriented at angles intermediate to the horizontal and vertical axes. (3) Displacements in oblique directions might be smaller in magnitude than displacements in horizontal and vertical directions.…”
mentioning
confidence: 99%
“…Stimulus discrimination is likewise superior in the horizontal and vertical meridians (Bowker, 1980b;Matin & Drivas, 1979;Taylor, 1963). In addition, the apparent contrast (Bowker & Mandler, 1981) and length (Ritter, 1917;Thompson & Schiffman, 1974)of a stimulus depends on its orientation.…”
mentioning
confidence: 99%
“…There is virtually no effect of orientation at spatial frequencies at or below 4 cpd (see also Berkley, Kitterle, & Watkins, 1975). Nevertheless, other suprathreshold data have shown orientation effects in which it can be inferred that lateral interactions are weaker in the oblique orientations with large targets and at medium spatial frequencies (Bowker & Mandler, 1981;Kitterle, 1973). In addition, other research (Kitterle & Thomas, 1980) indicates that at higher spatial frequencies the effect of orientation on alternation rate is not found.…”
mentioning
confidence: 83%